Bedensel engelli milli paralimpik sporcuların karşılaştıkları zorluklar ve hukuki ihtiyaçlarının incelenmesi - Vural, Engin (Muş Alparslan Üniversitesi, 2025)
Bu çalışmanın amacı bedensel engelli milli paralimpik sporcuların karşılaştıkları zorluklar ve hukuki ihtiyaçlarının incelenmesidir. Çalışmada derinlemesine bilgi toplamak amacıyla nitel araştırma yöntemlerinden fenomonoloji deseni kullanılmıştır. Araştırmanın evrenini 2020 Tokyo Paralimpik Oyunlarına katılan 57 bedensel engelli sporcu oluşturmaktadır. Örneklemi ise, amaçlı örnekleme yöntemiyle seçilen 40 bedensel engelli sporcu oluşturmaktadır. Veriler, araştırmacı tarafından uzman görüşleri doğrultusunda oluşturulan 10 ana görüşme sorusu ve 7 sondaj sorusundan oluşan yarı yapılandırılmış görüşme formu aracılığıyla, Zoom platformu üzerinden toplanmıştır. Araştırma verileri MAXQDA 24 programı aracılığı ile içerik analizi ile analiz edilmiştir. Analiz sonucunda 8 ana tema ve 11 alt temaya bağlı 168 kod oluşturulmuştur. Katılımcıların, milli olmadan önce ve milli olduktan sonra ulaşım, malzeme yetersizliği ve ekonomik destek gibi konularda sorunlar yaşadığı saptanmıştır. Spor tesislerinde engelli dostu düzenlemelerin yapılması, psikolojik desteğin tüm federasyonlar tarafından her zaman sağlanması gerekliliği bulgulanmıştır. Antrenörlerin ve diğer ekibin istisnalar olmasıyla birlikte büyük ölçüde yeterli olduğunu saptanmıştır. Yetenekli engelli sporcuların yetiştirilmesi için yetenek taramaları gibi faaliyetlerin yapılması gerektiği saptanmıştır. Sporcuların sponsor ve menajer bulmakta zorlandıkları saptanmıştır. Sporcu sözleşmelerinden dolayı büyük çoğunluğun sorun yaşamadığı fakat bazı sporcuların sorun yaşadıkları bulgulanmıştır. Emeklilik hakları kapsamında sporu bıraktıktan sonra tazminat ödenmesi ve şeref aylığının yetersizliğinden dolayı artırılması gerektiği saptanmıştır. Hukuki haklar kapsamında derece alamayan milli sporculara da maaş bağlanması, tüm sporculara sigorta yapılması, engelli sporcuların öğretmen olarak atanma haklarının genişletilmesi, resmi yazı ve prosedürlerin kolaylaştırılması gerektiği bulgulanmıştır. Ödül yönetmeliği kapsamında ödüllerin artırılması ve zamanında verilmesi, sekiz ülke kuralında düzenleme yapılması gerektiği saptanmıştır. Sosyal haklar kapsamında tekerlekli sandalye ve protezlerde daha fazla destek verilmesi, engelli otoparklarına ulaşımın kolaylaştırılması, araç alımı için Özel Tüketim Vergisi ve medikal malzemelerde indirimlerin yapılması gerektiği saptanmıştır. Engelli sporcular için iş istihdamının artırılması, temel ihtiyaçlara ilişkin tüm faturalarda (elektrik, doğalgaz vb.) indirim yapılması, daha fazla ekonomik destek sağlanması gerekmektedir. Son görüşler kapsamında sporu bıraktıktan sonra antrenörlük yolunun açılması gerektiği, spor yapmanın özgüven sağladığı, daha fazla paralimpik sporcunun yetiştirilmesi gerektiği saptanmıştır. Sonuç olarak sporcuların milli olmadan önce ve milli olduktan sonra fiziksel altyapı, sosyal, ekonomik ve hukuki açıdan birtakım zorluklar ile karşılaştıkları belirlenmiştir. Paralimpik milli sporcuların istekleri doğrultusunda düzenlemelerin yapılmasının milli organizasyonlarda sporcuların motivasyon ve performanslarını artıracağı düşünülmektedir.

The aim of this study is to examine the challenges encountered and the legal needs experienced by nationally recognized Paralympic athletes with physical disabilities. In order to collect in-depth information, the phenomenological design, one of the qualitative research methods, was employed in this study. The population of the study consists of 57 athletes with physical disabilities who participated in the 2020 Tokyo Paralympic Games. The sample consists of 40 athletes with physical disabilities selected through purposive sampling. The data were collected via the Zoom platform using a semi-structured interview form consisting of 10 main interview questions and 7 probing questions, which were developed by the researcher based on expert opinions. The research data were analyzed through content analysis using the MAXQDA 24 software program. As a result of the analysis, 168 codes were generated under 8 main themes and 11 sub-themes. It was determined that the participants experienced challenges related to transportation, insufficient equipment, and financial support both before and after becoming national athletes. The findings revealed the necessity of implementing disability-friendly arrangements in sports facilities and ensuring the continuous provision of psychological support by all sports federations. It was determined that, with some exceptions, coaches and other support staff were largely adequate. It was determined that activities such as talent identification screenings are necessary for the development of skilled athletes with disabilities. It was found that athletes face difficulties in securing sponsors and managers. While the majority reported no issues related to athlete contracts, some participants indicated that they had encountered problems in this regard. It was determined that, within the scope of retirement rights, compensation should be provided after athletes retire from sports and that the honorary pension is insufficient and therefore needs to be increased. Within the scope of legal rights, it was found that salary payments should also be extended to national athletes who do not achieve rankings, all athletes should be provided with insurance, the right of athletes with disabilities to be appointed as teachers should be expanded, and official documentation and procedures should be simplified. Within the scope of the award regulations, it was determined that the amount of awards should be increased and delivered in a timely manner, and that revisions to the eight-country rule are necessary. Within the scope of social rights, it was determined that greater support should be provided for wheelchairs and prosthetic devices, access to disabled parking should be facilitated, and reductions should be applied to Special Consumption Tax for vehicle purchases as well as to the cost of medical supplies. It is necessary to increase employment opportunities for athletes with disabilities, apply discounts to all utility bills (such as electricity and natural gas), and provide greater financial support. In the context of final opinions, it was determined that a pathway to coaching should be made available after retirement from active sports, that participation in sports enhances self-confidence, and that there is a need to train a greater number of Paralympic athletes. As a result, it was identified that athletes face various challenges related to physical infrastructure, social conditions, economic support, and legal rights both before and after becoming national athletes. It is believed that implementing regulations in line with the demands of Paralympic national athletes will enhance their motivation and performance in national competitions.
Examination of the challenges and legal needs of physically disabled nati̇onal paralympic athletes
Keywords: Spor; Sports